A Neutral Risk on the Development of New-Onset Diabetes Mellitus (NODM) in Taiwanese Patients with Dyslipidaemia Treated with Fibrates - Chien-Ying Lee; Kuang-Hua Huang; Chun-Che Lin; Tung-Han Tsai; Hung-Che Shih (The Scientific World Journal)
There are no data on the incidence of new-onset diabetes mellitus (NODM ) in nondiabetic dyslipidaemia patients treated with fibrates. The aim of our study was to clarify these issues, to investigate the relationship between NODM and fibrate and whether the fibrates lead to increased risk for developing NODM. A retrospective cohort study was conducted by analyzing the Longitudinal Health Insurance Database (LHID 2005) of the National Health Insurance Research Database (NHIRD) from 2005 to 2010 to investigate all fibrate prescriptions for patients with dyslipidaemia. We estimated the hazard ratios (HRs) of NODM associated with fibrate use. We identified 145 NODM patients among 3,815 dyslipidaemic patients in the database for the study period. The risk estimates for NODM for users of fenofibrate (HR 1.30; 95% CI 0.82, 2.05) and gemfibrozil (HR 0.771; 95% CI 0.49, 1.22) were not associated with an increased risk of developing NODM (P>0.05). Our results revealed that patients with dyslipidaemia who took fenofibrate and gemfibrozil had a neutral risk of NODM. The reasons may be associated with the fibrates have the properties that activate PPARα and in some cases also activated PPARγ, leading to showing a neutral risk of NODM.